READINESS OF MADRASAH IBTIDAIYAH TEACHERS TO FACE EDUCATIONAL DIGITALIZATION TOWARDS INDONESIA EMAS 2045 - Rahmah, Salsabila; Fauziah, Suci Fauziyah; Dwi Yunisa, Yeni; Farhurohman, Oman (PGMI UNHASY, 2026)
This study is based on the reality of madrasah ibtidaiyah (MI) teachers who play an important role in facing the wave of education digitalization towards the vision of Indonesia Emas 2045. Through a literature review of 20 scientific articles published between 2015 and 2025, this study highlights the readiness of madrasah teachers in integrating technology into learning. The results of the analysis show that most teachers are still in the early stages of adaptation, where technology is used only as a substitute for conventional methods, not yet achieving innovative pedagogical transformation. Factors that influence digital readiness include technological literacy, infrastructure support, education policy, and the sustainability of training. The gap between urban and rural teachers is also significant, particularly in terms of internet access and digital facilities. This study offers a conceptual model of madrasah teacher readiness that emphasizes four main variables: digital pedagogical competence, technological knowledge, infrastructure support, and sustainable policies. Thus, this study contributes to the development of basic education science by emphasizing that digitization is not merely the modernization of tools, but a systematic transformation that requires collaboration between teachers, institutions, and the government to create an adaptive golden generation in the digital age.